2020
DOI: 10.1155/2020/8843759
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Artificial Intelligence Methods for Condition Monitoring and Fault Diagnosis of Rolling Element Bearings for Induction Motor

Abstract: The fault detection and diagnosis (FDD) along with condition monitoring (CM) and of rotating machinery (RM) have critical importance for early diagnosis to prevent severe damage of infrastructure in industrial environments. Importantly, valuable industrial equipment needs continuous monitoring to enhance the safety, reliability, and availability and to decrease the cost of maintenance of modern industrial systems and applications. However, induction motor (IM) has been extensively used in several industrial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 224 publications
1
58
0
Order By: Relevance
“…A lot of research has been conducted in the past on the diagnosis of holes or dents in the bearing raceways and it has been shown that a small-sized hole (diameter < 1 mm) can produce tinny amplitudes; it is thus a great challenge to reliably diagnose these small faults [ 26 , 27 , 28 , 29 , 30 ]. Some studies have used noise filtration and threshold-based statistical analysis algorithms to enhance the reliability of the small-sized hole diagnostics [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of research has been conducted in the past on the diagnosis of holes or dents in the bearing raceways and it has been shown that a small-sized hole (diameter < 1 mm) can produce tinny amplitudes; it is thus a great challenge to reliably diagnose these small faults [ 26 , 27 , 28 , 29 , 30 ]. Some studies have used noise filtration and threshold-based statistical analysis algorithms to enhance the reliability of the small-sized hole diagnostics [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current decade, the use of artificial intelligence (AI) has been significantly increased for the reliable diagnostics and classification of machine faults [ 29 ]. AI techniques such as machine learning and deep learning can be trained to accomplish specific tasks by processing a large amount of data and recognizing fault trends in them [ 30 , 31 , 32 ]. There are various types of algorithms for machine learning and deep learning and the selection of the algorithm is a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…However, this manual method not only requires a lot of manpower, material, and financial resources but also ensures that the fault can be eliminated in time. With the development of computer technology, large-and medium-sized motors are equipped with computer-centered condition monitoring and fault diagnosis system, in order to prevent or repair the functional failure or local failure before the failure, minimize the loss, and prevent the occurrence of catastrophic accidents [2].…”
Section: Introductionmentioning
confidence: 99%
“…Induction motors are mainly used in residential and industrial applications such as transportation, mining, chemicals, power plants, and paper for electrical to mechanical energy conversion [1] due to their high reliability, robustness, and costeffectiveness. However, the main issue with the operation of induction motors is that such harsh industrial application has affected their reliability, causing unexpected breakdowns, resulting in high maintenance costs and motor deterioration [2,3].…”
Section: Introductionmentioning
confidence: 99%